Thoracoscopic resection of a paraaortic bronchogenic cyst - Acri Ignazio; Micali Vincenzo; La Rocca Annunziata; Sibilio Michele; Monaco Francesco; Barresi Pietro; Familiari Dario; Lentini Salvatore; Mondello Baldassare; Barone Mario; Monaco Maurizio (Journal of Cardiothoracic Surgery, 2010)
Abstract Bronchogenic mediastinal cysts (BMC) represent 18% of primitive mediastinal tumors and the most frequent cystic lesions in this area. Nowadays, BMC are usually treated by VATS. However, the presence of major adhesions to vital structures is often considered as an unfavourable condition for thoracoscopic treatment. The authors report the thoracoscopic treatment of a BMC having dense adhesions to the aortic arch. Diagnosis and surgical treatment is described. Review of the literature and surgical options on this topic are discussed.